Primary care micro-teams: an international systematic review of patient and healthcare professional perspectives - Coombs, C; Cohen, T; Duddy, C; Mahtani, KR; Owen, E; Roberts, N; Saini, A; Foster, AS; Park, S (Royal College of General Practitioners, 2023)
Background: International trends have shifted to creating large general practices. There is an assumption that interdisciplinary teams will increase patient accessibility and provide more cost-effective, efficient services. Micro-teams have been proposed to mitigate for some potential challenges of practice expansion, including continuity of care. Aim: To review available literature and examine how micro-teams are described, and identify opportunities and limitations for patients and practice staff. Design and setting: This was an international systematic review of studies published in English. Method: Databases (MEDLINE, EMBASE, CINAHL, Cochrane Library, and Scopus) and grey literature were searched. Studies were included if they provided evidence about implementation of primary care micro-teams. Framework analysis was used to synthesise identified literature. The research team included a public contributor co-applicant. The authors conducted stakeholder discussions with those with and without experience of micro-team implementation. Results: Of the 462 studies identified, 24 documents met the inclusion criteria. Most included empirical data from healthcare professionals, describing micro-team implementation. Results included characteristics of the literature; micro-team description; range of ways micro-teams have been implemented; reported outcomes; and experiences of patients and staff. Conclusion: The organisation of primary care has potential impact on the nature and quality of patient care, safety, and outcomes. This review contributes to current debate about care delivery and how this can impact on the experiences and outcomes of patients and staff. This analysis identifies several key opportunities and challenges for future research, policy, and practice.